MYRTUS COMMUNIS IMPROVES COGNITIVE IMPAIRMENT IN RENOVASCULAR HYPERTENSIVE RATS - ŞEN, ALİ; YEGEN, BERRAK; ERTAŞ, BÜŞRA; ŞENER, GÖKSEL; KOYUNCUOĞLU, TÜRKAN (POLISH PHYSIOLOGICAL SOC, 2020)
Myrtus communis has anti-inflammatory, neuroprotective and anticholinesterase activities yet there have been limited studies examining effects of Myrtus communis on cognitive functions. This study investigated the possible effects of Myrtus communis on changes in the cognitive functions of experimental renovascular hypertensive rats. Fifty-six Wistar-Albino rats were equally divided into 4 groups; sham-operated control, renovascular hypertension (RVH), ramipril (RVH + Ram) and Myrtus communis extract (RVH + MC) treatment groups. Goldblatt's 2-kidney 1-clip (2K1C) method was used to induce RVH. At the end of 9 weeks of treatment, after blood pressure recording, the animals underwent new object recognition test and Morris water maze (MWM) task. Following these tests, blood brain barrier (BBB) integrity was examined in 6 animals from each group. In the others after decapitation, osteopontin and interleukin (IL)-10 levels were measured in blood samples; while matrix metalloproteinase (MMP)-13, sodium potassium adenosine triphosphatase (Na+,K+-ATPase), cluster of differentiation (CD) 36, amyloid beta (Ab), neprilysin levels, and acetylcholinesterase (AChE) activity were investigated in hippocampal tissues. In RVH group, high systolic blood pressure decreased serum IL-10 levels, increased serum osteopontin levels and also impaired BBB permeability. Hippocampal MMP-13, CD36, Ab, neprilysin levels and AChE activities were elevated, while there were decreases in Na+,K+-ATPase levels. In new objet recognition test, discrimination index (DI) was determined as lower in saline-treated RVH group compared to control animals. In MWM training trail, 4th day performance in finding platform was significantly reduced in saline-treated RVH group compared to control group. RVH also decreased the time spent in target quadrant in probe test of MWM task compared to control group. In both of the treatment groups, all biochemical parameters were restored in parallel with improvement in the behavioral test performances. The results of this study suggest that Myrtus communis extract may improve the cognitive dysfunctions in hypertension through antihypertensive, anti-inflammatory and anticholinesterase activities.
Keywords: renovascular hypertension; cognitive impairment; blood brain barrier; angiotensin II; ramipril; Myrtus communis; amyloid beta; osteopontin; acetylcholinesterase; ANGIOTENSIN-CONVERTING ENZYME; BRAIN-BARRIER IMPAIRMENT; OSTEOPONTIN EXPRESSION; ALZHEIMERS-DISEASE; OXIDATIVE STRESS; MEMORY FUNCTION; ESSENTIAL OIL; STROKE; INHIBITORS; DYSFUNCTION